Sugar and slaves : the rise of the planter class in the English West Indies, 1624-1713 - Dunn, Richard S.; Nash, Gary B. (Chapel Hill [North Carolina] ; London [England] : Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2000)
Sugar and Slaves presents a vivid portrait of English life in the Caribbean more than three centuries ago. Using a host of contemporary primary sources, Richard Dunn traces the development of plantation slave society in the region. He examines sugar production techniques, the vicious character of the slave trade, the problems adapting English ways to the tropics, and the appalling mortality rates for both blacks and whites that made these colonies the richest, but in human terms the least successful, in English America.
Foreword; Preface; Abbreviations; 1 Beyond the Line; 2 Barbados: The Rise of the Planter Class; 3 Barbados: The Planters in Power; 4 The Leeward Islands; 5 Jamaica; 6 Sugar; 7 Slaves; 8 Life in the Tropics; 9 Death in the Tropics; 10 The Legacy; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Slavery -- West Indies, British; Plantation life -- West Indies, British; West Indies, British -- Social life and customs; West Indies -- History -- 17th century; Vie dans les plantations -- Antilles britanniques; Antilles -- Histoire -- 17e siècle.; Antilles britanniques -- Mœurs et coutumes; Manners and customs; Plantation life; Slavery; West Indies; West Indies -- British West Indies; Plantation life -- West Indies, British; Slavery -- West Indies, British; Sugar -- Manufacture and refining -- West Indies, British; West Indies, British -- Social life and customs; West Indies -- History -- 17th century; 1600-1699; History